The role of visioning in business network strategizing - Abrahamsen, Morten H.; Halinen, Aino; Naudé, Peter (Journal of business research, 2023)
•Defines the concept of visioning and conduct an empirical study on its role in business network strategizing.•Presents an abductive qualitative case study from a business network by comparing the forward-looking and backward-looking perspectives of managers at two points in time.•Reveals what managers can foresee, what limits their visioning and ultimately to what extent visioning informs strategic action.•Findings suggest that visioning helps managers to openly contemplate the future, to envisage structural changes, detect probable trends and form strategic intentions but individual cognitive frameworks and network constraints limit their visioning.•Proposes a conceptual model of business network strategizing where visioning forms an important step in between reflection and networking and by showing how managers consciously prepare for the future. Visioning the future is an essential aspect of strategizing. However, how managers make sense of their networked business environment, future changes in it, and how this visioning informs their interaction and networking has hardly been explored. Drawing on organizational foresight and business network research, we enhance the visioning concept by conducting an abductive qualitative case study on its role in business network strategizing. By comparing forward-looking and backward-looking perspectives of managers in companies within a particular business network, the study reveals what managers can foresee, what limits their visioning, and to what extent visioning informs network strategizing. Our findings suggest that visioning helps managers to openly contemplate the future, to envisage structural changes, detect probable trends, and form strategic intentions, but individual cognitive frameworks and network constraints limit their visioning. The study contributes to the current sensemaking view of network strategizing by proposing a conceptual model where visioning forms an important step in between reflection and networking, and by showing how managers consciously prepare for the future.